2021
DOI: 10.3390/molecules26185688
|View full text |Cite
|
Sign up to set email alerts
|

Novel c-Jun N-Terminal Kinase (JNK) Inhibitors with an 11H-Indeno[1,2-b]quinoxalin-11-one Scaffold

Abstract: c-Jun N-terminal kinase (JNK) plays a central role in stress signaling pathways implicated in important pathological processes, including rheumatoid arthritis and ischemia-reperfusion injury. Therefore, inhibition of JNK is of interest for molecular targeted therapy to treat various diseases. We synthesized 13 derivatives of our reported JNK inhibitor 11H-indeno[1,2-b]quinoxalin-11-one oxime and evaluated their binding to the three JNK isoforms and their biological effects. Eight compounds exhibited submicromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…The calculated ΔG° 298 values for the E out ·H 2 O → Z out ·H 2 O interconversion equal 6.1 and 12.1 kJ/mol for IQ-1 and Trp-Ox , while the TS·H 2 O microsolvates display Gibbs energies 194.5 and 190.4 kJ/mol above the corresponding E out ·H 2 O species formed by IQ-1 and Trp-Ox , respectively ( Figure 8 ). However, water solubilities of the investigated parent oximes are very low, and efforts were undertaken to synthesize more soluble derivatives like oximates of alkali metals [ 13 , 17 ] and compounds containing amine or carboxylic substituents in the benzene rings [ 19 ] of IQ-1 and Trp-Ox .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated ΔG° 298 values for the E out ·H 2 O → Z out ·H 2 O interconversion equal 6.1 and 12.1 kJ/mol for IQ-1 and Trp-Ox , while the TS·H 2 O microsolvates display Gibbs energies 194.5 and 190.4 kJ/mol above the corresponding E out ·H 2 O species formed by IQ-1 and Trp-Ox , respectively ( Figure 8 ). However, water solubilities of the investigated parent oximes are very low, and efforts were undertaken to synthesize more soluble derivatives like oximates of alkali metals [ 13 , 17 ] and compounds containing amine or carboxylic substituents in the benzene rings [ 19 ] of IQ-1 and Trp-Ox .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, for sodium salt of IQ-1 known as IQ-1S, an antihypertensive effect associated with the attenuation of blood viscosity and a decrease in endothelin-1 production was reported [ 18 ]. Several derivatives of IQ-1 with the substituents in the aromatic rings inhibited lipopolysaccharide (LPS)-induced nuclear factor-κB/activating protein 1 (NF-κB/AP-1) activation and interleukin-6 (IL-6) production, which is important for anti-inflammatory activity [ 19 ]. Nie et al demonstrated that IQ-1S protected the mice from sepsis through inhibiting the JNK signaling pathway [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, flat ring structures have been identified as kinase-specific privileged structures; i.e., compounds containing these fragments are enriched for kinase targets, compared with other target classes ( Posy et al, 2011 ). Thus, although oxime side groups may contribute important interactions in the JNK binding site ( Schepetkin et al, 2012 ; Schepetkin et al, 2015 ; Schepetkin et al, 2019 ; Liakhov et al, 2021 ; Schepetkin et al, 2021 ), the tetracyclic nucleus seems to be responsible for proper ligand positioning. Docking experiments performed in the present study and in our previous work ( Schepetkin et al, 2019 ) show that the tryptanthrin nucleus stipulates good complementarity of the ligands to the JNK1-3 binding sites with similar orientations of the tetracyclic moiety.…”
Section: Resultsmentioning
confidence: 99%
“…All complexes had chiral ruthenium(II) centers but crystallized in centrosymmetric space groups and thus enantiomer resolution was not possible. Polycyclic IQ-1 derivatives look promising as ligands in terms of stabilizing the complexes due to π-π stacking interactions and their biological properties [28][29][30][31]. In the present paper, the IQ-1 ligand was used to prepare new half-sandwich cyclopentadiene iridium(III) and rhodium(III) complexes, and for the rhodium(III) coordination compound, a spontaneous resolution of enantiomers was observed.…”
Section: Introductionmentioning
confidence: 86%